Some properties of a certain class of rational functions - Raina, R.K.; Bansal, D.K. (Applied mathematics and computation, 2007)
In the present paper, we investigate the familiar geometric properties of starlikeness, convexity and spirallikeness of a certain class of rational functions. Relevance with various known (and new) results are also mentioned.